Women admitted to Lady Reading Hospital, Peshawar who are Breast Feeding their infants under 6 months age - Mujtaba Gul, Muhammad Abbas, Sohaib, Razia, Amjad Ali, Zakir Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: A top objective for worldwide public health is exclusive breastfeeding for the first six months of life. There is evidence that a number of factors, including women’s claimed reasons for discontinuing nursing, are related to early termination of breastfeeding. Aim: To describe women’s reported intentions to breastfeed and actual nursing patterns as well as to look at relationships between various parameters at Lady Reading Hospital, Peshawar. Methodology: This convergent design “to obtain different but complementary data on same topic” to best understand the research problem was conducted after ethical approval at lady reading hospital peads OPD & ward from June 2018 to June 2019. 129 feeding mothers were enrolled in the study. Educational history, employment and marital status, feeding position with knowledge, postpartum depression and medication history were noted. Result: Highest ratio of 151(69%) were seen in age <35. Primary level education 118(54%) were seen more than other parameters. Employment ratio was seen less in working mothers 87(40%). Highest ratio of not giving answer 19 was seen in store milk while same view for breast milk first food after delivery was same for all. 22 mothers responded same answer for water use. Depression was seen in 97 mothers while 89 were safe and 33 didn’t answer. Colostrum was given to 137 infants while hygienic care in washing hand was seen in 107(48%). Medication used for lactation was used by 40(18%) mothers. Practical implication of this study is to share maximum knowledge to the feeding mothers which will help socially in sharing the same in their homes and societies. The mothers and child health is basic foundation for their home, society and country. Conclusion: Hygienic care is important for both mother and infant. Education and help assistance is useful after first delivery. Post natal depression should be monitored and health care providers should give visits to all pre natal mothers for education and hygienic care guidance. Keywords: Breast feeding, infant, mothers, education, hygiene care, traditions and culture